(untitled) (World Bulletin of Social Sciences, 2023)
This article examines the importance and effectiveness of using chemical experiments in the teaching of organic chemistry in general secondary schools. The article provides information on how the use of experiments contributes to a deeper understanding of the basic principles of organic chemistry by students. An analysis of literature sources and studies was carried out, and the effectiveness of using chemical experiments in increasing students’ interest and passion for learning organic chemistry was determined